What’s on the (publication fee) menu, who pays the bill and what should be the venue? - TSIKLIRAS, A. C.; STERGIOU, K. I. (Mediterranean Marine Science, 2013)
We address the cost of access to knowledge and its ethical implications in ‘true’, ‘pseudo’ and ‘hybrid’ OA journals.